2022
DOI: 10.1186/s12889-022-13103-1
|View full text |Cite|
|
Sign up to set email alerts
|

Factors affecting family planning literacy among women of childbearing age in the rural Lake zone, Tanzania

Abstract: Background Low uptake of various recommended modern family planning methods is associated with inadequate family planning literacy among potential beneficiaries of the methods. As such, understanding factors affecting family planning literacy is key to addressing this problem. This study, therefore, explored factors affecting family planning literacy among women of childbearing age in the rural Lake Zone of Tanzania. Methods The study utilized an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
1
16
0
1
Order By: Relevance
“…The results of research conducted in Tanzania found that religious beliefs affect family planning literacy. Some religions forbid them to use contraception because it is considered to prevent the meeting of egg and sperm cells so that pregnancy does not occur, and this is against God's will (Kassim and Ndumbaro, 2022). The results of another study conducted in Nigeria by Ai, Odejimi O and Ad (2018) on 104,884 women of childbearing age-aged 15-45 years, stated that 84.5% of family planning decisions were influenced by the husband's acceptance of contraceptive methods.…”
Section: Discussionmentioning
confidence: 99%
“…The results of research conducted in Tanzania found that religious beliefs affect family planning literacy. Some religions forbid them to use contraception because it is considered to prevent the meeting of egg and sperm cells so that pregnancy does not occur, and this is against God's will (Kassim and Ndumbaro, 2022). The results of another study conducted in Nigeria by Ai, Odejimi O and Ad (2018) on 104,884 women of childbearing age-aged 15-45 years, stated that 84.5% of family planning decisions were influenced by the husband's acceptance of contraceptive methods.…”
Section: Discussionmentioning
confidence: 99%
“…This message should be delivered at the most convenient time for rural women. In a Tanzanian study, rural women admitted that sometimes such information was disseminated through various mass media sources such as radio, but at a time when they were too busy with household responsibilities to get the information (29).…”
Section: Discussionmentioning
confidence: 99%
“…Education has been identified as a path to empowerment over a woman’s reproductive health, holistic well-being, and it raises awareness of the benefits and drawbacks of contraceptives (24). Rural women in a Tanzanian study claimed that their low levels of education made it difficult for them to understand family planning information from various sources (29). Evidence suggests that education improves women’s knowledge and attitudes toward modern contraceptive use (30).…”
Section: Discussionmentioning
confidence: 99%
“…Education has been identi ed as a path to empowerment over a woman's reproductive health, holistic well-being, and it raises awareness of the bene ts and drawbacks of contraceptives (24). Rural women in a Tanzanian study claimed that their low levels of education made it di cult for them to understand family planning information from various sources (29). Evidence suggests that education improves women's knowledge and attitudes toward modern contraceptive use (30).…”
Section: Discussionmentioning
confidence: 99%